Evaluation of the face advance rate on ground control in the open face area associated with mining operations in Western China. (10th February 2020) - Song, Gaofeng; Wang, Zhenwei; Ding, Kuo
Abstract: The modern longwall faces in coal bases in Western China are being mined at an increasingly faster rate, yet the consequences of the face advance rate on the ground control and strata movement require further investigation. In this study, two improved physical models with different advance rates are developed to evaluate the roof failure characteristics; the strata movement; the displacement of the strong, massive roof; and the roof movement velocity. The results show that: (i) regular falls of the immediate roof and major falls of the hard roof are observed with the progressive development of the longwall face. Massive fractures on the roof strata extending from the face to the ground surface develop on a major roof fall. (ii) Model I, which has a slower face advance rate, shows a major roof fall interval of 65 m, which is slightly less than the 70 m found by Model II, which advances at a faster rate. Larger strata fractures are observed in Model I, while the gob area of Model II is better filled with waste rock materials. (iii) The displacement and velocity of the hard roof are unnoticeable until a massive roof fall. Maximum displacement occurs on a major roof fall, which is 50 mm for Model I and 30 mm for Model II. The maximum roof movement velocity on a major roof fall is 4.6 cm per min and 5.9 cm per min for Models I and II, respectively.